PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 26 PADANG - Mahendra, Adelia (Jurnal Edukasi dan Penelitian Matematika, 2023)
Good math communication abilities are expected in math. As observed in the field, class VIII students at SMP Negeri 26 Padang in 2023/2024 had inadequate mathematical communication abilities. The Think Talk Write (TTW) learning paradigm was used to solve problems. This research analyzes students' math communication skills when teaching with TTW model, which is superior to conventional learning, and describes how those skills develop from the model. The non-equivalent posttest-only control group design is used in this quasi-experimental descriptive research. The quiz and final test assessed mathematical communication. Normal distribution and homogenous variance are required for the t-test data analysis. Analysis of quiz data showed all indices of students' mathematical communication developed. P-value <α rejects H0, indicating the TTW cooperative model impacts communication abilities.Keywords–Mathematical Communication Skills, TTW,  Conventional Learning